Analysis of the incidence of breast cancer in the Krasnoyarsk Territory - R. A. Zukov; I. P. Safontsev; A. V. Zyuzyukina; K. D. Permyakova; T. N. Zamay; A. S. Kichkaylo (Опухоли женской репродуктивной системы)
Aim. To conduct an analysis of the incidence of breast cancer in the Krasnoyarsk Territory for 2012–2021 and calculate the medium-term forecast of indicators until 2030.   Materials and methods. An analysis of the incidence of breast cancer in the Krasnoyarsk Territory was performed using the Microsoft Office Excel 2021 program. A calculation was made of “rough” indicators of oncological incidence of breast cancer, calculated per 100,000 population of the corresponding sex and age. Forecasting the incidence of breast cancer was carried out among the population of residents of Krasnoyarsk and the Krasnoyarsk Territory (excluding the city of Krasnoyarsk), of the following type: y = b + ax, where y is the predicted incidence of lung cancer; х is the serial number of the year of observation, starting from the initial reference point (2012); b is a constant; a is a coefficient reflecting the average change in y with an increase in x by one unit; and the approximation coefficients R2 were also determined.   Results and conclusion. The incidence of breast cancer during the study period increased both in the regions of the Krasnoyarsk Territory and in the city of Krasnoyarsk by 21.36 % and 19.05 %, respectively. Age-specific analysis of the incidence of breast cancer in the female population showed that the incidence in Krasnoyarsk in the age group of 20–24 years showed the maximum increase, the maximum decrease in incidence was observed in the age group of 25–29 years. In the regions of the Krasnoyarsk Territory, the maximum increase in this indicator is observed in the age group of 40–44 years, and the maximum decrease in the age group of 30–34 years. The share of early detection among the working-age population is higher in the regions of the Krasnoyarsk Territory and amounts to 4.7 % over a 10-year period. The share of early detection among the working-age population is higher in the regions of the Krasnoyarsk Territory and amounts to 4.7 % over a 10-year period. The proportion of early detection among women of the disabled population is higher in Krasnoyarsk, but there is a decrease of 0.97 %. According to prognostic estimates, by 2030 the incidence of breast cancer will increase by 1.2 times in the regions of the Krasnoyarsk Territory and in the city of Krasnoyarsk. The largest increase in the incidence is predicted in the female population of the city of Krasnoyarsk – by 1.24 times compared to 2021 and by 47.8 % compared to 2012. To overcome the growth, it is necessary to introduce new technologies and methods for early diagnosis and monitoring the effectiveness of anticancer therapy.